Detention - Doroclea, Andreea Denisa (Eximia, 2023)
Preventive measures at present may be ordered only if there is evidence or well-founded character from which there is a reasonable suspicion that the individual has committed a criminal act and is necessary to achieve the aim pursued by taking them. The categories of preventive measures, with the exception of detention and preventive arrest, are changed, defending judicial control, judicial control on bail and house arrest compared to the old regulation which referred to the obligation not to leave the locality and the obligation not to leave the country together with detention and preventive arrest. Procedural aspects are extremely important in this preventive measure, such as the communication under signature of the detained person, of his/her rights and obligations, the duration for which he/she can be detained and, in certain special cases, informing the diplomatic representatives of the state of which the suspect or accused person is a citizen. In the case of certain persons, the law also requires certain additional requirements to be met in order to order detention, such as in the case of deputies or senators or judges, prosecutors or assistant magistrates. The measure of detention is the most used preventive measure and that it has a particular effect on the suspect as well as on the course of the trial. As it has a special status, being the only measure that can only be ordered during criminal investigations, I think it is very important to be aware of it. Detention is a preventive measure in the procedure of which numerous procedural errors can occur, so we considered necessary a thorough study to clarify all aspects of this preventive measure.